The Role of Human Resource Competence in Improving the Quality of MSMEs Towards Halal and Green Economy: - - Trisninawati, Trisninawati; Aliya, Sabeli; Heriyanto, Heriyanto; Maulina, Mia; Wati, Bungsu Widias (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This international community service aims to improve the competence of MSME human resources in managing businesses based on halal principles, helping MSMEs understand how to move towards halal and implementing Green Economy practices in their business lines. The Green Economy approach aims to improve human welfare and social justice while reducing the risk of environmental damage and resource scarcity. Using the ABCD (Asset Based Community Development) approach targeting MSME stakeholders fostered by the Bandung Regency Regional Development Research and Innovation Planning Agency (Bapperida). The results of this Community Service show that the application of the principle of resource efficiency in the context of a green economy by MSME actors fostered by the Bandung Regency Regional Development Research and Innovation Planning Agency (Bapperida) has made significant progress, although there are still challenges to be faced. Through interviews with several MSME owners, it was revealed that they have begun to implement efficient practices in the use of raw materials and waste management. By continuously striving to improve environmentally friendly practices, MSMEs will not only strengthen their position in the market but also play an active role in preserving the environment for future generations